2018
DOI: 10.3390/coatings8040141
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Composite Langmuir Films via Fluorine-Containing Bola-Type Derivative with Metal Ions

Abstract: The design and preparation of functional bolaamphiphile-based composite films are of key importance for application in a wide variety of fields. This study demonstrates a new approach to constructing composite films by the Langmuir-Blodgett (LB) method using a fluorine-containing bola-type diacid derivative with different metal ions. The bola-type molecule we used could be spread on water surfaces and metal ion subphases to fabricate various nanostructured ultrathin films. The obtained data demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…At the same time, ions of trivalent cations tend to hydrolysis and complexation more than divalent metals in an overwhelming number of cases; therefore, this problem is more relevant for trivalent ions. In this regard, works on these lanthanide salts were published much later, in spite of the fact that the production of such films was described in literature and results of the preparation multilayer LBF from acids and trivalent metals were reported. , The techniques often used to obtain these structures are not standard and have only been studied for a small number of trivalent cations. Despite the fact that yttrium is formally trivalent, the formation of films proceeded with ease, as with films containing ordinary divalent cations. Yttrium stearate was studied in ref , where it was shown that the ion fraction form of the yttrium content in the film depends on the pH of the subphase.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, ions of trivalent cations tend to hydrolysis and complexation more than divalent metals in an overwhelming number of cases; therefore, this problem is more relevant for trivalent ions. In this regard, works on these lanthanide salts were published much later, in spite of the fact that the production of such films was described in literature and results of the preparation multilayer LBF from acids and trivalent metals were reported. , The techniques often used to obtain these structures are not standard and have only been studied for a small number of trivalent cations. Despite the fact that yttrium is formally trivalent, the formation of films proceeded with ease, as with films containing ordinary divalent cations. Yttrium stearate was studied in ref , where it was shown that the ion fraction form of the yttrium content in the film depends on the pH of the subphase.…”
Section: Introductionmentioning
confidence: 99%